Effect of Cognition Recovery by Repetitive Transcranial Magnetic Stimulation on Ipsilesional Dorsolateral Prefrontal Cortex in Subacute Stroke Patients - Kim, Jongwook; Cha, Byoungwoo; Lee, Doyoung; Kim, Jong Moon; Kim, MinYoung (Frontiers in Neurology, 2022)
Objective To demonstrate the efficacy of high-frequency repetitive transcranial magnetic stimulation (rTMS) over the ipsilesional dorsolateral prefrontal cortex (DLPFC) on neurological recovery in patients with subacute phase stroke. Methods Patients with supratentorial hemispheric stroke who were hospitalized for intensive rehabilitation in the subacute phase were enrolled for this retrospective analysis. Two groups of patients were selected: the rTMS group who received high-frequency (20 Hz) rTMS ≥ 5 times over the ipsilesional DLPFC, and a control group who did not receive any rTMS. The patients were further divided into groups with right- or left-side brain lesions. Functional measurements for cognitive ability, mood, speech, and activities of daily living, which were assessed at baseline and at the 1-month follow-up as a routine clinical practice, were used for analyses. Results Among 270 patients with available clinical data, 133 (women, 51; age, 61.0 ± 13.8 years) met the inclusion criteria and were enrolled for analysis. There were no differences in demographic data and functional scores at baseline between the rTMS (n = 49) and control (n = 84) groups. The rTMS group showed a higher gain in the mini-mental status examination (MMSE) total score and subscores of all domains, forward digit span, and FIM-cognition than the control group (P < 0.05). Among the patients with left hemispheric lesions (n = 57), the rTMS group showed better outcomes in cognition and depression through scores of total and “attention and concentration” subscores of MMSE, FIM-cognition, and the geriatric depression scale (P < 0.05). Among the patients with right hemispheric lesions (n = 76), the rTMS group showed better outcomes in cognition through the MMSE total score and subscores of “attention and concentration,” “registration,” and “recall,” and scores of both forward and backward digit spans (P < 0.05). Conclusion High-frequency rTMS over the ipsilesional DLPFC has beneficial effects on the recovery of cognition on both sides as well as mood in patients with left-sided hemispheric lesions.